Imunopatogenesis Karsinoma Mamae - Donaliazarti (CV. AKBAR PUTRA MANDIRI, 2024)
Malignant tumors that originate in the breast tissue are breast cancer. Breast cancer is the most common cancer in women and is the main cause of death in women between 40 and 59 years of age. Risk points for developing mammary carcinoma include age, gender, ethnicity, hormones, previous history of cancer, environmental exposures, diet, and inflammation. Breast cancer can have different characteristics even though it arises from the same cell type. Based on the presence or absence of ER, breast cancer is divided into ER- breast cancer and ER+ breast cancer. The change of normal cells into cancer is a complex process and consists of at least two phases, namely initiation and promotion. Cancer-related genes are divided into three categories: oncogenes, tumor suppressor genes, and genes that regulate apoptosis. Mutations in these genes can cause normal breast cells to become cancerous. The immune system acts as immunosurveillance needed to recognize and destroy abnormal cells before they develop into tumors or kill them if they have already grown. A new paradigm on the interaction of the immune system and tumor cells developed the immunoediting hypothesis. The immunoediting process consists of three phases: elimination, equilibrium and escape. Immunopathogenesis of breast cancer needs to be known as a basis for the development of future management.